Sulphate resistance of oil palm shell lightweight aggregate concrete containing palm oil fuel ash - Zaisyahirafifi, Abu Bakar (2014)
The ever popular issues of environmental preservation and sustainability all over the world has led to innovations of new materials using by-products generated from various sectors. Oil palm shell (OPS) is a waste material obtained during the extraction of palm oil by crushing of the palm nut in the palm oil mills. It is one of the most abundantly produced waste materials in South Asia. While, palm oil fuel ash (POFA) is a wastage from the palm oil industry which is disposed at the landfill. In this study, the durability performance of OPS lightweight aggregate concrete containing POFA as a partial cement replacement upon sulphate attack is determined. The replacement of cement by different percentage of POFA ranges from 0% to 40%. The sulphate resistance test of OPS lightweight aggregate concrete containing POFA is conducted by preparing 100mm cubes. After the cubes were water cured for 28 days, it was placed in sodium sulphate solution which prepared according to ASTM C 1012-04 for several weeks. The influences of POFA content in OPS concrete on physical changes, mass change and strength loss were determined. The results revealed that, there is no physical changes occurred along the short period weeks of immersion. Mix produced using 20% POFA exhibit the lowest mass change value and highest residual compressive strength after exposure to sulphate solution. Use of 20% POFA has lead to densification of OPS lightweight aggregate concrete internal structure through better pozzolanic reaction that taken places. Conclusively, 20% of POFA is the best recommended amount to be used as partial cement replacement to produced OPS lightweight aggregate concrete with better durability.